Development of the nervous system of Aplysia californica. - Kriegstein, A R (1977)
The ability to grow the marine molluse Aplysia under laboratory conditions allows a detailed study of the formation of the nervous system and of the development of specific identified cells. I have found that the ganglia develop in a specific temporal order. Cerebral and pedal ganglia develop at hatching, the abdominal, pleural, and osphradial ganglia 3 weeks after hatching, and the buccal ganglia at 4 weeks. The origin of the abdominal ganglion is complex; its anlage forms at 3 weeks from three larval ganglia that fuse to form the abdominal ganglion. Individual cells cannot be distinguished from one another by their location within the ganglion or by their appearance alone until metamorphosis at 5 weeks. After metamorphosis, the identified neuron, R2, suddenly becomes recognizable because of a significant increase in its size.